Meanings of body and health in the context of modern life styles - Aguilar Martínez, Dania Oralia (2020)
DOI: 10.26439/persona2020.n023(1).4833 The social representations of the body and health were explored using semantic networks and a semi-structured questionnaire in university students of low socioeconomic status. Diet, exercise, hygiene and medical care are the most important elements of the representation of health. The meanings of the body are associated with gender stereotypes, which have an impact on health care, thus highlighting the importance of recognizing the attributes, abilities and manifestation of the body as human characteristics, as well as the intrinsically social character of the body and health and not reduce it to the individual and physical environment.